Drug-induced hypomethylation of a posttranscriptionally silenced transgene locus of tobacco leads to partial release of silencing - Kovarík, A; Van Houdt, H; Holý, A; Depicker, A (FEBS letters, 2000)
The effect of DNA methylation upon posttranscriptional gene silencing (PTGS) has been investigated in transgenic tobacco lines showing PTGS and methylation of the neomycin phosphotransferase II (nptII) reporter genes. Application of the hypomethylation drugs dihydroxypropyladenine or 5-azacytidine resulted in approximately 30% reduced methylation of cytosines located in a non-symmetrical context in the 3' untranslated region of the nptII transgenes. The hypomethylation was accompanied by up to 12-fold increase in NPTII protein levels, suggesting that methylation of non-symmetrical motifs may account for an increased degree of PTGS. Models for the possible role of DNA methylation in PTGS are discussed.
Keywords: Cytosine; DNA Methylation; transgeny; Adenine; Kanamycin Kinase; metylace DNA; Transcription, Genetic; reportérové geny; umlčování genů; adenin; kanamycinkinasa; Azacitidine; 3' nepřekládaná oblast; regulace genové exprese u rostlin; Plants, Toxic; genetická transkripce; kultivované buňky; DNA, Bacterial; jedovaté rostliny; DNA bakterií; Plants, Genetically Modified; Nicotiana; otevřené čtecí rámce; Gene Expression Regulation, Plant; cytosin; 3' Untranslated Regions; Open Reading Frames; geneticky modifikované rostliny; Cells, Cultured; Gene Silencing; Transgenes; Genes, Reporter; tabák; azacytidin